Determinants of Employee Engagement and Productivity: An Analysis of Work Motivation, Competence, Compensation and Transactional Leadership - Agustian Zen (East Asian Journal of Multidisciplinary Research, 2023)
This scientific  article  aims to show that the variables in the  field of  human  resources offered  in this scientific article reinforce through the existing review literature, by looking at and presented in a result of the author's perspective. The recommendation of this  scientific article is that it can  be continued in   this variable  can be used by  other researchers together   into one variable in a   research result.